A Mathematical Model For The Population Dynamics Of Disease Transmiting Vectors in Particular Female Anopheles Mosquitoes. - Turyamusiima, Richard (Kabale University, 2024)
In this paper we present a mathematical model of population dynamics of female anopheles mosquitoes. The threshold dynamics of this model is determined and the stability of equilibrium points have been obtained using the jacobian matrix. The mosquito free equilibrium and endemic equilibrium have been determined by setting system of ordinary differential equations to zero. Basic reproduction has been determined using the next generation matrix management analyzed. Hence. we show that if the threshold dynamics quantities are less than unity, the mosquitos' population decreases to zero but if they are greater than unity, mosquitos' population persists.